From Empire to Republic Post-World War I Austria - Bischof, Günter (Contemporary Austrian Studies, 2010)
The 18 essays in this volume offer innovative scholarship on the difficult transition from empire to republic for the small state of Austria, newly created by the Allied peacemakers in Paris in 1919. They also deal with the complex challenges posed by nation building after a major war, including the ambiguity inherent in the creation of new institutions in politics, economics, social life, and culture. In 1919 the government of the fledgling Republic of Austria was confronting revolutionary turmoil in the streets of Vienna, a near-total collapse of the agricultural and industrial economies, and the fallout of a crushing military defeat. In addition, the government was overburdened by the sheer number of new veterans, including the over 100,000 wounded soldiers returning from the frontlines. The redrawn Austrian borders produced a loss of German ethnics and major demographic shifts. Austrians-no longer dominant in a vast empire-were uncertain of their standing. In spite of ideological conflict between the major political camps, Austria experienced a cultural and educational revival-one that proved essential to forging a new national identity.